2022
DOI: 10.1111/bjd.21232
|View full text |Cite
|
Sign up to set email alerts
|

miR ‐378a regulates keratinocyte responsiveness to interleukin‐17A in psoriasis*

Abstract: The study was approved by the Stockholm Regional Ethics Committee and conducted according to the Declaration of Helsinki principles. Written informed consent was obtained from all participants prior to enrolment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In this issue of the BJD, Xia and colleagues systematically investigated the interplay between miR-378a and IL-17A in human keratinocytes. 6 Sequencing of small RNAs showed miR-378a to be overexpressed in keratinocytes isolated from lesional psoriatic skin compared with nonlesional psoriatic skin and healthy skin, a finding that was also previously published by the same group. 7 In a psoriasis mouse model, intradermal injection of miR-378a was found to exacerbate psoriasis-like skin inflammation, suggesting that increased levels of miR-378a in psoriatic keratinocytes contribute to the pathogenesis.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…In this issue of the BJD, Xia and colleagues systematically investigated the interplay between miR-378a and IL-17A in human keratinocytes. 6 Sequencing of small RNAs showed miR-378a to be overexpressed in keratinocytes isolated from lesional psoriatic skin compared with nonlesional psoriatic skin and healthy skin, a finding that was also previously published by the same group. 7 In a psoriasis mouse model, intradermal injection of miR-378a was found to exacerbate psoriasis-like skin inflammation, suggesting that increased levels of miR-378a in psoriatic keratinocytes contribute to the pathogenesis.…”
supporting
confidence: 64%
“…In this issue of the BJD , Xia and colleagues systematically investigated the interplay between miR‐378a and IL‐17A in human keratinocytes 6 . Sequencing of small RNAs showed miR‐378a to be overexpressed in keratinocytes isolated from lesional psoriatic skin compared with nonlesional psoriatic skin and healthy skin, a finding that was also previously published by the same group 7 .…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Psoriasis is a multifaceted, chronic inflammatory skin disorder characterized by a complex pathogenesis, in which ncRNA classes, such as long ncRNAs and especially miRNAs, have been established to be deregulated and to play essential roles [ 15 , 48 , 54 56 ]. In addition, we have previously shown that global circRNA abundance is decreased in lesional relative to non-lesional skin of psoriatic patients [ 16 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miR-203a-3p was shown to be enriched in psoriatic skin lesions and to possess a critical role in disease progression by targeting genes involved in epidermal differentiation, such as p63 [ 63 ] and SOCS-3 [ 15 ], and in immune responses with targets like pro-inflammatory cytokines TNFα and IL-24 encoding transcripts [ 47 ]. In a recent study [ 56 ], miR-378a ectopic overexpression, mimicking the miRNA increase in psoriasis, was found to promote p63 transport to the nucleus and further contributed to the IL-17A-mediated activation of NF-κB pathway signaling by acting as suppressor of NFKBIA . While miR-378a was not included in the miRNA NanoString panel used in this study, we found miR-378i to be deregulated in skin biopsies.…”
Section: Discussionmentioning
confidence: 99%